Islamic outdoor education: Peningkatan pemahaman konsep tauhid pada anak-anak TPA Nuruz Zahroh Kelurahan Dukuh - Perdani, Landy Alya Putri; Fitriana, Fatikha Nur; Indriasari, Suci; Faidi, Ahmad (Nur Science Institute, 2025)
This community service aims to determine the application of the Participatory Action Research (PAR) method with outbound activities for children of TPQ Nuruz Zahroh in Dukuh Village. This community service applies a cooperative learning model of the Teams Games Tournament (TGT) type through Islamic Outbound activities that integrate Islamic values to strengthen cooperation’s moral and ethical foundations. The subjects of this study were children at TPQ Nuruz Zahroh, totalling 50 children, located in Dukuh Village. The method used in this teaching is Islamic Outdoor Education, which aims to actively involve the community in every activity. Data collection techniques used include observation and documentation. The results of the community service show that the application of the Participatory Action Research (PAR) community service method with outbound activities for children of TPQ Nuruz Zahroh developed well in terms of cooperation, socialization, and building self-confidence in children. The results can be seen from the outbound activities that ran smoothly and successfully. The outbound activities went through several stages, namely, planning things that must be prepared for the Islamic Outbound game. Implementing Islamic Outbound activities consists of several games, such as Islamic trail, faith relay, and straw relay.